The Quality of Infrastructure Facilities and the Readiness of Biology Laboratories to Support Learning in High School - Sholikhah, Mei Renni; Agustina, Lina (Universitas Muhammadiyah Surakarta, 2023)
Biology learning is the mastery of collecting knowledge information in concepts, principles, and facts, as well as learning and comprehending how the process of acquiring knowledge is achieved directly through the practicum. Physical and social skills can be developed through the use of practicum activities as a learning supplement. The implementation of practicum activities must be supported by a high-quality laboratory infrastructure. The laboratory equipment and infrastructure of Cal must comply with the laboratory requirements outlined in Permendiknas Number 24 of 2007. The research aimed to determine the quality of infrastructure facilities and the readiness of biology laboratories to support learning at SMA Negeri 1 Cawas. This research is qualitative descriptive research through observation, interviews and documentation. The results showed that the quality of biological laboratory infrastructure based on Permendiknas Number 24 of 2007 was included in the perfect category with an average percentage of 95%. Meanwhile, laboratory readiness obtained an average readiness percentage value of 92%, including in the ready category, so the biology laboratory in this school is ready to be used to support learning.